The first scientific collection of insects from Siam. (3rd April 2023) - Hawes, Timothy C.
ABSTRACT: Siamese specimens were among those included in the historically significant insect descriptions made by Johan Christian Fabricius in the 18th century. The full extent of this collection and its provenance are largely unknown. A collation of described specimens from Fabricius, identified 29 species of Insecta attributed to Siam. A species list, with current nomenclature, is provided. Two beetles of primarily temperate origins are considered doubtful. Another two taxa are currently taxonomically misdated. Although all these specimens were attributed to the Joseph Banks insect collection, where they remain, the original source of the specimens is identified by Fabricius' letters as the botanist, Jean Gerard Koenig. From material not described, or misattributed, by Fabricius, four additional lepidopterans have documented historical provenance linking them to Siam, while 21 more have probable and/or potential links to the type locality. The collecting observations of Koenig are discussed and described. From these it is also possible to identify exact capture records of several species. As well as linking the starting point for entomological science in Thailand with the historical origins of insect taxonomy, the collated descriptions represent the first insect species list for the country.